2012
DOI: 10.2340/16501977-0920
|View full text |Cite
|
Sign up to set email alerts
|

Effect of forced use therapy on posture in children with hemiplegic cerebral palsy: A pilot study

Abstract: This pilot study showed that forced use therapy may be an efficient way to improve postural asymmetry in children with hemiplegic cerebral palsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Two upper limb intervention studies were identified, each using a different approach: constraint‐induced movement therapy or force use therapy (see Table SIIa). Both studies were classified as level IV (demonstrating low levels of evidence), and, therefore, did not meet criteria for further evaluation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two upper limb intervention studies were identified, each using a different approach: constraint‐induced movement therapy or force use therapy (see Table SIIa). Both studies were classified as level IV (demonstrating low levels of evidence), and, therefore, did not meet criteria for further evaluation.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, there were no high-level upper limb interventions suitable for reporting at this stage. Ballaz et al 65 contend that investigating postural control outcomes following constraint-induced movement therapy and force use therapy is important to assess the effect of reducing asymmetric upper limb function on balance (postural stability) and postural symmetry (orientation). More rigorous research is required before it is possible to recommend these approaches specifically as effective postural control interventions.…”
Section: Discussionmentioning
confidence: 99%
“…The non-dominant hand is considered to be the less functional, more involved hand in children with spastic diplegic and quadriplegic CP. Forced use of the more involved hand in children with hemiplegia has been shown to decrease postural asymmetry after a 12-day intervention (24); however, similar research has not been conducted on children with bilateral spastic CP. The bimanual interface potentially gave children with spastic diplegia and quadriplegia the opportunity to use their more involved extremities, thus decreasing postural asymmetry.…”
Section: Discussionmentioning
confidence: 99%
“…During the intervention, the children wore a sling on the non-involved upper limb. After FUT, upper limb functional scores improved significantly, and postural asymmetry tended to decrease, compared with the pre-therapy values 10 . Wen-Hsiu Yu et al proposed that FUT can be used on lower extremity on gait performance and mobility of post-acute stroke patients.…”
Section: Discussionmentioning
confidence: 78%
“…FUT is similar to constraints induced movement therapy. An aim of FUT is encouraging spontaneous use of affected limb in daily activities 10 .…”
Section: Introductionmentioning
confidence: 99%